Gestational trophoblastic disease in a Greenlandic Inuit: diagnosis and treatment in a remote area. (6th May 2016) - Dalsgaard Jensen, Trine; Penninga, Luit
Abstract : We report on a 21-year-old pregnant Greenlandic Inuit woman, who presented at a small local hospital in Northern Greenland. The patient suffered from lower abdominal pain, irregular bleeding and vomiting. urine-human chorionic gonadotropin (U-hCG) was positive. Ultrasonography showed the typical 'snow-storm' images of a mole pregnancy. Owing to the fact that local physicians were able to perform an ultrasound, proper diagnosis could be established, and the patient was transferred to the regional hospital, located nearly 1200 km away. At the regional hospital, uterine evacuation was performed under general anaesthesia. Blood analysis showed that serum hCG returned to undetectable levels, and the patient recovered uneventfully. Our case shows that ultrasonography is a valuable diagnostic tool also in remote areas. In Greenland, geographical distances are large and weather conditions can be extreme, and in this report, we discuss how healthcare can be optimised in remote areas.